Out of Gay, and Into Class Closet: On Politics of Identity and Reflexive Sociology in Didier Eribon and Éduard Louis: Conversation Between Kate Korycki and Anna Zawadzka - Anna Zawadzka; Kate Korycki (Studia Litteraria et Historica, 2018)
The conversation starts with an in-depth analysis of two autobiographical works, Returning to Reims by Didier Eribon (2013) and The End of Eddy by Éduard Louis (2017). The discussion concerns, among other things, the double exclusion due to non-heteronormativity and class origin. Does gay emancipation occur exclusively within dominating social classes? What is the price of emancipation for individuals from dominated classes? Is it possible to come to terms with the stigma of being both gay and of working class origin? Why has the problematization of heteronormativity been abundantly represented in literature and arts, whereas that of classism continues to be a taboo as a subject of both autobiographies and academic studies?